1992
DOI: 10.1038/bjc.1992.255
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of mdr1 gene expression in leukaemic cells from patients with acute leukaemia

Abstract: Summary By using a quantitative RNA-RNA solution hybridisation method, the average number of mdrl RNA transcripts per cell was measured in total nucleic acid extracts of leukaemic cells from patients with acute leukaemia. The results in different types of leukaemia were (number of patients with detectable mdrl RNA/total number of patients; median number of transcripts per cell in samples with detectable mdrl RNA); de novo untreated acute myelocytic leukaemia (AML): 20/44; 0.7, secondary acute myelocytic leukae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 36 publications
4
17
2
Order By: Relevance
“…Apoptosis, which was evaluated after 18 h, was determined from caspase 3 activation and phosphatidylserine exposure using flow cytometry. Attempts have also been made to find correlations between in vitro drug uptake, P-gp expression, and clinical outcome [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis, which was evaluated after 18 h, was determined from caspase 3 activation and phosphatidylserine exposure using flow cytometry. Attempts have also been made to find correlations between in vitro drug uptake, P-gp expression, and clinical outcome [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Using immunohistochemical methods (Musto et al, 1990) or immunoblot techniques (Kuwazuru et al, 1990) P-170 expression was found in six out of 12 and in four out of 11 adult ALL patients respectively. In addition, increased MDR-J mRNA transcripts were found in five of 14 adults with ALL (Gruber et al, 1992). In a recent work Goasguen et al (1993) found P-170 expression in 12 out of 36 children (33%) with newly diagnosed ALL.…”
Section: Discussionmentioning
confidence: 99%
“…K562/Vcr3O and K562fVcrl50 expressed approximately 100 and 200 mdrl mRNA transcripts per cell, respectively, as determined by a quantitative RNAase protection assay (Gruber et al, 1992 Leukaemic cells Peripheral leukaemic cells from ten patients with AML were used. Cells isolated on Lymphoprep (Nycomed, Pharma, AS, Norway) were frozen in a programmed freezer and kept in liquid nitrogen.…”
Section: Materials and Methods Cell Linesmentioning
confidence: 99%
“…The viability of the cells after thawing was controlled with trypan blue exclusion and was 70% and 73% in two samples; in the remaining, the viability was over 85%. The samples were chosen according to their mdrl mRNA expression, which was determined earlier with a quantitative RNAase protection assay (Gruber et al, 1992). Cells from five of the patients had no detectable mdrl mRNA levels, and cells from five patients had mdrl mRNA levels ranging from 1.0 to 3.8 mdrl mRNA transcripts per cell.…”
Section: Materials and Methods Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation